Representasi Tokoh Perempuan dalam Film 3 Srikandi Karya Iman Brotoseno: Kajian Analisis Wacana Kritis Norman Fairclough - Hair, Muhammad; Ernanda, Ernanda; Izar, Julisah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This research aims to find out and understand how female characters are represented in the film 3 Srikandi using Norman Fairclough's critical discourse analysis approach. The primary data source in this research is the feature film 3 Srikandi by Iman Brotoseno. The second source of data in this research is writing which contains information about the true story of the character Srikandi which is relevant to the research topic and interviews with sources who made the film 3 Srikandi. Data collection techniques were carried out by watching films periodically, changing films in the form of transcriptions, and conducting interviews with the screenwriter of the film 3 Srikandi to find out the film production process. Data analysis was carried out in three stages, namely text analysis, discourse practice analysis and sociocultural analysis. At the text analysis stage, 34 linguistic feature data were found that were used to represent women, including 15 rhetorical question data, 11 repetition data, 6 cynicism data and 2 symbolic data. In discourse practice, the text production section shows that this film wants to appreciate female athletes who have contributed to Indonesia and introduce to the public that there are three Indonesian women who won their first medals in the sport of archery. Meanwhile, text consumption shows that this film wants to show how the female characters struggle to achieve victory, shows the problems of women who want freedom to determine their own dreams and life choices, and conveys the message that to become a successful athlete you have to go through hard training, discipline, sacrifice and struggle. Then, in the sociocultural analysis of the film 3 Srikandi, we want to convey that women are individuals who also have rights and freedoms in society. Women also have the right to make their own choices and make their dreams come true. Through this film, it is hoped that society will no longer look at gender in terms of providing opportunities and support for each individual. Abstrak Penelitian ini bertujuan untuk mengetahui dan memahami bagaimana representasi tokoh perempuan dalam film 3 Srikandi menggunakan pendekatan analisis wacana kritis Norman Fairclough. Sumber data utama dalam penelitian ini adalah film layar lebar 3 Srikandi karya Iman Brotoseno. Sumber data kedua dalam penelitian ini yaitu tulisan yang memuat informasi mengenai kisah nyata dari tokoh Srikandi yang relevan dengan topik penelitian dan wawancara dengan narasumber pembuat film 3 Srikandi. Teknik pengumpulan data dilakukan dengan menonton film secara berkala, mengubah film dalam bentuk transkripsi, dan melakukan wawancara dengan penulis skenario film 3 Srikandi untuk mengetahui proses produksi film. Analisis data dilakukan melalui tiga tahapan, yaitu analisis teks, analisis praktik wacana dan analisis sosiokultural. Pada tahapan analisis teks ditemukan 34 data fitur linguistik yang digunakan untuk merepresentasikan perempuan, diantaranya 15 data pertanyaan retoris, 11 data repetisi, 6 data sinisme dan 2 data simbolik. Pada praktik wacana, bagian produksi teks menunjukkan bahwa film ini ingin mengapresiasi sosok atlet perempuan yang telah berjasa untuk Indonesia dan memperkenalkan pada masyarakat bahwa terdapat tiga perempuan Indonesia yang meraih medali pertama melalui cabang olahraga panahan. Sementara konsumsi teks menunjukkan film ini ingin menampilkan bagaimana perjuangan para tokoh perempuan meraih kemenangan, memperlihatkan permasalahan perempuan yang ingin kebebasan dalam menentukan impian dan pilihan hidup sendiri, serta menyampaikan pesan untuk menjadi atlet yang sukses harus melalui latihan keras, disiplin, pengorbanan dan perjuangan. Kemudian pada analisis sosiokuktural film 3 Srikandi ingin menyampaikan bahwa perempuan merupakan individu yang juga memiliki hak dan kebebasan dalam kehidupan masyarakat. Perempuan juga berhak untuk menentukan sendiri pilihannya dan mewujudkan impiannya. Melalui film ini masyarakat diharapkan tidak lagi memandang gender dalam hal memberikan kesempatan dan dukungan pada setiap individu.